Public Priorities and Preferences for End-of-Life Care in Namibia - Powell, Richard A.; Namisango, Eve; Gikaara, Nancy; Moyo, Sherperd; Mwangi-Powell, Faith N.; Harding, Richard (Journal of pain and symptom management, 2014)
Although quality end-of-life care provision is an international public health issue, the majority of evidence is not generated in low- and middle-income countries that bear a disproportionate burden of progressive illnesses.To identify the priorities and preferences of the Namibian public for end-of-life care.Using a cross-sectional study design, data were collected in the country's capital, Windhoek, from November to December 2010. In total, 200 respondents were recruited. The mean age was 27 years (SD 7.5; range 18–69), with nearly all (n = 199; 99.5%) expressing a religious affiliation. Being in pain was reported as the most concerning of nine common end-of-life symptoms and problems (n = 52; 26.1%), and the most important care-related aspect was having as much information as wanted (n = 144; 72%). The majority (64%) would want their end-of-life care to focus on improving their quality of life rather than extending it, with 40% not wanting to know if they had limited time left to live. Hospital (n = 96; 48%) and home (n = 64; 32%) were the most preferred places of death. The most important end-of-life priority was keeping a positive attitude (n = 128; 64%). Having had a close relative or friend diagnosed with a serious illness was associated with a 2.3 increase in the odds of preference for a hospital death (odds ratio = 2.34, P = 0.009, 95% CI 1.23–4.47).This study identified a number of areas that need to be pursued in future research to explore factors that may affect patient preferences and priorities in end-of-life care in Namibia.
Keywords: Namibia, Africa, end of life, terminal, cancer